2014
DOI: 10.1002/ardp.201400233
|View full text |Cite
|
Sign up to set email alerts
|

Novel Capsaicin Analogues as Potential Anticancer Agents: Synthesis, Biological Evaluation, and In Silico Approach

Abstract: A novel class of benzo[d][1,3]dioxol-5-ylmethyl alkyl/aryl amide and ester analogues of capsaicin were designed, synthesized, and evaluated for their cytotoxic activity against human and murine cancer cell lines (B16F10, SK-MEL-28, NCI-H1299, NCI-H460, SK-BR-3, and MDA-MB-231) and human lung fibroblasts (MRC-5). Three compounds (5f, 6c, and 6e) selectively inhibited the growth of aggressive cancer cells in the micromolar (µM) range. Furthermore, an exploratory data analysis pointed at the topological and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
(40 reference statements)
1
17
0
4
Order By: Relevance
“…21,22 The experimental data on the capsaicin chemical modification-mediated cytotoxic potential against cancer cells are limited. 23,24 A previous study found that the RPF101 capsaicin-like analogue exhibits higher antitumour activity than capsaicin by inducing arrest of the cell cycle at the G2/M phase through disruption of the microtubule network in MCF7 cells. 23 Piperonylamine was sulfonylated by benzenesulfonyl chloride to yield RPF101 with more suitable lipophilic properties and a hydrogen bond acceptor character, which are relevant features for improved pharmacokinetic and pharmacodynamic profiles.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 The experimental data on the capsaicin chemical modification-mediated cytotoxic potential against cancer cells are limited. 23,24 A previous study found that the RPF101 capsaicin-like analogue exhibits higher antitumour activity than capsaicin by inducing arrest of the cell cycle at the G2/M phase through disruption of the microtubule network in MCF7 cells. 23 Piperonylamine was sulfonylated by benzenesulfonyl chloride to yield RPF101 with more suitable lipophilic properties and a hydrogen bond acceptor character, which are relevant features for improved pharmacokinetic and pharmacodynamic profiles.…”
Section: Discussionmentioning
confidence: 99%
“…7C) displayed potent growth-suppressive activity in TRPV1-OE cells, and this process was mediated by the ROS oxidative stress pathway (Thomas et al, 2007). Damião et al (2014) synthesized a variety of capsaicin analogs (Fig. 7, C-E) and tested for their cytotoxicity in B16F10 (mouse melanoma), SK-MEL-28 (human melanoma), NCI-H1299, NCI-H460 (human lung cancer), SK-BR-3, and MDA-MB-231 (human breast cancers) cell lines (Damião et al, 2014).…”
Section: Antineoplastic Activity Of Synthetic Capsaicin Analogsmentioning
confidence: 99%
“…A indução da exposição de calreticulina por CHY-1 . DAMIÃO et al, 2014;OVERINGTON;NARANG;DESAI, 2009;PALACE-BERL et al, 2015;TEIXEIRA et al, 2014). Neste contexto os fosfolipídios e as vias de produção destes surgem como um ponto de interesse devido as suas funções celulares e à presença de alterações relacionadas a eles e suas funções no contexto tumoral (IGAL, 2010;MENENDEZ;LUPU, 2007;RYSMAN et al, 2010;SCOTT et al, 2010;SWINNEN et al, 2003).…”
Section: 9unclassified